Kegagalan Jurnalisme Profesional dan Kemunculan Jurnalisme Publik - Puji Rianto (Program Studi Ilmu Komunikasi, 2007)
There are plenty of critics coming upon the professional journalism or on the journalism that rises up the objectivity and neutrality. Professional journalism is believed has failed to cover the democratization of political system and citizens. On the other hand, attempts on running over the objectivity and neutrality make it trapped on the higher orientation, to the public figures. In facing those kind of weakness, public journalism is coming over it The basic orientation is how journalism ought to make itself as easy as possible for citizens to make intelligent decisions about public affairs, and to get them carried out